Critically ill neonates displayed stable vital parameters and reduced metabolic acidosis during neonatal emergency airborne transport in Sweden. (26th March 2018) - Frid, Ingrid; Ågren, Johan; Kjellberg, Mattias; Normann, Erik; Sindelar, Richard
Abstract: Aim: This study evaluated the medical quality of acute airborne transports carried out by a neonatal emergency transport service in a Swedish healthcare region from 2012 to 2015. Methods: The transport charts and patient records of all infants transported to the regional centre were reviewed for transport indications and vital parameters and outcomes. Results: We identified 187 acute airborne transports and the main indications for referral were therapeutic hypothermia after perinatal asphyxia, extremely preterm birth and respiratory failure. There were 37 deaths, but none of these occurred during transport and none of the deaths that occurred within 24 hours after transport were found to be related to the transport per se . No differences were found in vital parameters or ventilator settings before and after transport, except for an improvement in blood pH (7.22 ± 0.13 versus 7.27 ± 0.13, mean ± SD, p < 0.01), due to a decrease in base deficit (−8.0 ± 6.8 versus −5.4 ± 6.3 mmol, p < 0.001), while the partial pressure of carbon dioxide remained unchanged. Conclusion: During air transport, critically ill neonates displayed stable vital parameters and reduced metabolic acidosis. No transport‐related mortality was found, but the high number of extremely preterm infants transported indicates the potential for improving in‐utero transport.